THE ALGORITHMIC GAZE: A REVIEW OF HOW ARTIFICIAL INTELLIGENCE IN OPHTHALMOLOGY IS SHAPING CLINICAL DECISION-MAKING AND THE PATIENT-DOCTOR RELATIONSHIP - Maja Ćwiek, (International Journal of Innovative Technologies in Social Science, 2025)
The incorporation of artificial intelligence (AI) into ophthalmology represents a paradigm shift, not just technologically but socially, reshaping diagnostic processes and the core of the clinical encounter. This comprehensive review examines how AI technologies are transforming ophthalmic practice, focusing on their dual impact on clinical workflows and the fundamental nature of the patient-doctor relationship. Through analysis of current literature, we explore the applications of AI in diagnosing diabetic retinopathy, glaucoma, and age-related macular degeneration, where many systems demonstrate diagnostic accuracy rivaling experts. Crucially, we investigate the socio-technical dynamics of physician trust in AI, examining automation bias and the potential for deskilling. Patient perceptions and acceptance of AI-mediated care are analyzed, highlighting concerns about the preservation of human connection. The review concludes by discussing ethical considerations and proposing frameworks for the responsible integration of AI that leverages technological advancements to improve outcomes while preserving the core values of patient-centered care.